(untitled) (International Journal of Engineering and Computer Science, 2023)
This work is carried out to produce eco-friendly disinfectants from renewable sources to obey the clarion call for climate revival. Two bio-disinfectants, 2-3-dihydroxyl propanal (glyceraldehyde) and ortho-cresol (o-cresol) were synthesized from dry leaves of Gmelina arborea using barium chloride catalyst and distilled water at 60 oC. The products obtained were analyzed using GC-MS. The yield of 2-3-dihydroxyl propanalobtained at reaction temperatures of 10, 20, 30, 40, 50 and 60 oC were 2.94, 5.51, 5.47, 5.55, 11.61, and 1.14%, respectively. Similarly, the yields of ortho-cresol, at the corresponding reaction time, were 4.76, 8.14, 8.40, 7.63, 10.05, and 18.31%, respectively. The production of these two bio-disinfectants from biodegradable waste material has helped in the utilization and recycling of waste leaves into useful materials and also protects the environment and the entire ecosystem.